Methods of Forming the Environmental Communicative and Legal Literacy of Primary Class Students - Khuzhamurodova Khosiyat Panjiyevna; Abduraimova Nilufar (International Journal on Integrated Education, 2022)
The article describes the formation of environmental competence among elementary school students, the formation of environmental legal literacy among elementary school students in interactive ways, the process of developing personal legal literacy qualities, the formation of environmental legal literacy in the classroom and extracurricular environmental activities.